2009
DOI: 10.1002/lary.20233
|View full text |Cite
|
Sign up to set email alerts
|

Repair of the tympanic membrane with urinary bladder matrix

Abstract: Objectives/Hypothesis-To test urinary bladder matrix (UBM) as a potential treatment for tympanic membrane (TM) healing and regeneration.Study Design-This prospective pilot study was designed to provide both qualitative and semiquantitative assessment of temporal and spatial healing events in the chinchilla model of chronic TM perforations with and without UBM patching.Methods-Bilateral myringotomies were performed and repeated as necessary to create subtotal perforations over an 8-week period. Myringoplasty wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 23 publications
1
48
0
1
Order By: Relevance
“…33 The specific molecules within the UBM degradation products that are responsible for the effects reported herein are unknown. ECM facilitates constructive remodeling in a variety of tissues, 29,[34][35][36][37][38][39] and endogenous progenitor/stem cells participate in this process. 6,40 Bioactive degradation products of ECM promote the migration of a variety of cell types, including terminal Schwann cells, 41 endothelial cells, 42 and the perivascular stem cell population used in this present study.…”
Section: Discussionmentioning
confidence: 99%
“…33 The specific molecules within the UBM degradation products that are responsible for the effects reported herein are unknown. ECM facilitates constructive remodeling in a variety of tissues, 29,[34][35][36][37][38][39] and endogenous progenitor/stem cells participate in this process. 6,40 Bioactive degradation products of ECM promote the migration of a variety of cell types, including terminal Schwann cells, 41 endothelial cells, 42 and the perivascular stem cell population used in this present study.…”
Section: Discussionmentioning
confidence: 99%
“…ECM materials are at the forefront of biomaterial research and have been successfully used in a diverse range of medical applications [13][14][15]. As our understanding of these materials increases, it is becoming more apparent that they possess many properties that would make them ideal for use in vascular tissue engineering.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…The aim of this study is to compare the endothelialisation of the most commonly employed graft coating clinically; fibrincoated expanded polytetrafluoroethylene (ePTFE) with novel decellularised xenogenic extracellular matrix (ECM) scaffolds. ECM scaffolds support the growth of several cell types [10][11][12] and have already proven successful in reconstructing a wide range of specialised tissues [13][14][15]. The ECM scaffolds we are examining are derived from the porcine urinary bladder wall -Urinary Bladder Matrix (UBM) and porcine jejunum -Small Intestine Submucosa (SIS).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] With recent rapid advances in regenerative medicine fields related to biomaterials, tissue engineering, drug delivery, and stem cell therapy, novel methods to heal TM perforations have been studied as alternatives to surgical repairs of TM perforations. Many researchers have attempted to regenerate TM using biomaterials, such as collagen, 6 hyaluronic acid, 7 Poly(B-benzyl-L-aspartate-co-L-leucine)50/50, calcium alginate, 9 silk, 10,11 chitosan, 3,12 AlloDerm, 2 or urinary bladder matrix, 13 which is based on the paper patch technique. These studies demonstrated that biomaterials as an artificial TM patch may play a role in potential therapy for healing TM perforations without surgical treatments.…”
Section: Introductionmentioning
confidence: 99%